Restructuring Traditional Islamic Education in Indonesia: Challenges for Pesantren Institution - Ervan Nurtawab; Dedi Wahyudi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
This article examines the current traditional Islamic education in Indonesian Islamic boarding schools, known as pesantren, following the passing of the pesantren bill into legislation by the Indonesian People’s Representative Council in September 2019. We focus on aspects of the Pesantren Legislation (Undang-Undang Pesantren), which recognises pesantren as a new type of formal education and regulates the way the pesantren system is managed. People who engage in the pesantren system will certainly take advantage of this legislation. Nevertheless, they cannot avoid possible changes of established values in pesantren that have been socially reproduced for a long time. The authors argue that in the first two decades of the 21st century, Indonesian traditionalist Muslims have celebrated an important development in the pesantren tradition-based education, which received formal recognition in Indonesia’s national education system.